Diseño de un sistema de costeo ABC, para la empresa Fabrilfame S.A. - Vásconez Criollo, Ricardo Xavier (2013)
This thesis presents a proposal to the company Fafrilfame S.A. for implementing the Activity Based Costing (ABC) system. It shows the principal impacts on the joint application with the method of production orders, to introduce a new picture of the costs of products, bringing them closer to the reality in the best way. The thesis presents information providing costs based on activities for decision-making and how to collaborate with the administrative levels to optimize resources and increase profitability. It also aims to find bottlenecks in processes and activities to be able to take corrective actions and to not move away from the objective of the business